Effects of Fire Frequency on Woody Plant Composition and Functional Traits in a Wet Savanna Ecosystem. (3rd November 2020) - Makumbe, Peter; Chikorowondo, Gift; Dzamara, Pride Canisia; Ndaimani, Henry; Gandiwa, Edson
Abstract : The objective of this study was to assess the effect of fire frequency on vegetation taxonomic and functional diversity in a wet savanna ecosystem, eastern Zimbabwe. The study area was stratified into three fire frequency regimes using a 15-year fire history (2000–2014) across the landscape: high (HFF: burnt every 1-2 years), medium (MFF: burnt every 3-4 years), and low (LFF: burnt every 5-6 years). Data were collected from a total of 30 plots measuring 20 m × 20 m each between March and May 2018. In each plot, we recorded tree maximum height ( H max ), woody plant density, basal diameter, resprouting capacity, and bark thickness. We calculated species evenness, diversity, functional richness (FRic), Rao's Quadratic Entropy (RaoQ), functional redundancy, and relative bark thickness. We recorded 1, 031 individual trees belonging to 24 species across the three fire regimes. Significant differences across the three fire regimes were recorded for H max, woody plant density, and relative bark thickness P < 0.05 . H max and woody plant density were higher in LFF than HFF regimes while relative bark thickness was higher in HFF than in the LFF regimes. Species evenness was significantly higher in HFF and MFF regimes than LFF regime P < 0.05, while FRic and functional redundancy significantly increased with decreasing fire frequency P < 0.05 . However, no significant differences were recorded for resprouting capacity, species richness, taxonomic diversity, and RaoQ P > 0.05 . Species like Cassia petersiana, Cussonia spicata, Vachellia spp., and Rhus lancea were associated with LFF, while species like Protea gaguedi, Brachystegia utilis, and Vangueria infausta showed a strong association with HFF to MFF. Our study demonstrated that a combination of taxonomic and functional diversity metrics is adequate to evaluate the response of savanna vegetation to fire. We recommend a further assessment on vegetation composition using other elements of fire regimes.